Hematopoietic Stem Cell Transplantation for Acute Myeloid Leukemia: An Overview of Systematic Reviews - Peijie He; Juan Liang; Wanjun Zhang; Shengyun Lin; Hanting Wu; Qiushuang Li; Xiujuan Xu; Conghua Ji (International Journal of Clinical Practice)
Background. Hematopoietic stem cell transplantation (HSCT) has become the main treatment for acute myeloid leukemia (AML) and has been studied in many systematic reviews (SRs), but strong conclusions have not been drawn yet. Objective. This study aimed to summarize and critically evaluate the methodological and evidence quality of SRs and meta-analysis on this topic. Methods. PubMed, Embase, the Cochrane Library, and Web of Science were searched for SRs/meta-analyses regarding HSCT for AML. Two reviewers assessed the quality of SRs/meta-analyses in line with AMSTAR-2 and evaluated the strength of evidence quality with the grading of the evaluation system (GRADE) for concerned outcomes independently. Results. 12 SR/Meta articles were included, and the AMSTAR-2 scale showed that the quality grade of all articles was low or very low. GRADE results showed 29 outcomes, 2 of which were high, 12 were moderate, and 15 were low. Limitations and inconsistency were the most important factors leading to degradation, followed by imprecision and publication bias. Allo-SCT had better OS and DFS benefits than auto-SCT and significantly reduced the relapse in intermediate-risk AML/CR1 patients. Auto-SCT was associated with lower TRM than allo-SCT but generally had higher relapse. The results should be confirmed further for the low or moderate evidence quality. Conclusion. Current SRs show that allo-SCT in the treatment of AML might improve the OS, RFS, and DFS. Auto-SCT has significantly lower TRM but higher RR. Whether bone marrow transplantation is superior to nonmyeloablative chemotherapy remains to be evaluated. Meanwhile, the quality of methodology needs to be further improved. The intensity of evidence was uneven, and the high-quality evidence of outcomes was lacking. Considering the limitations of our overview, more rigorous and scientific studies are needed to fully explore the efficacy of different interventions of HSCT in AML, and clinicians should be more cautious in the treatment.